BINDIND AND PERSUASIVES PRECEDENTS: THE LEGAL SECURITY AND THE COMMON LAW MECHANISMS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The present work aims to present a reflection on the insertion of precedents in the 2015 Code of Civil Procedure, and how this does not reflect the principle of legal certainty and the application of common law mechanisms in the creation and revision of precedents. To address the concepts of legal certainty, their contextualization, as well as a brief history of the origin of the precedents, understand from Portuguese languages ​​to date and the insertion of persuasive and binding precedents in the current CPC. The constant methodology of bibliographic research. The selected data were analyzed using the hypothetical deductive method. Finally, demonstrate whether the last chapter, in order for the legislator's intention to effect legal certainty and the insertion as precedents in the CPC, requires the intervention of common law mechanisms in the construction and revision of the precedents-the distingishing, overruling e a ratio decidendi.